MANAGEMENT OF EDUCATION INFRASTRUCTURE IN KATINGAN DISTRICT ELEMENTARY SCHOOLS - Parada; Ludang, Yetrie; Sion, Holten; Lion, Eddy; Tri Harinie, Luluk; Barbara, Betrixia (Acta Scientiae et Intellectus, 2024)
Educational facilities and infrastructure are all facilities used in the learning process, both mobile and immobile, so that the achievement of educational goals runs smoothly, regularly, effectively, and efficiently. School facilities and infrastructure will provide optimal benefits to students and teachers if their management is good. The management of facilities and infrastructure has to be carried out properly, services to all school members will increase in quality. Therefore, the management of facilities and infrastructure must be guided by existing references and practical problems faced by students and teachers. The headmaster is responsible for the existence of school facilities and infrastructure because it is directly related to the learning process in the school, while the manager is responsible for the organization and management of educational facilities and infrastructure. For the facilities and infrastructure to function optimally, it is necessary to manage both the management of buildings and equipment in schools.